Pulmonary and extrapulmonary complications associated with e-cigarette use: an integrative review (Research, Society and Development, 2022)
Objective: to investigate the pulmonary and extrapulmonary complications associated with the use of electronic cigarettes, considering their currently observed growth. Methodology: an integrative literature review was carried out during the years 2021 and 2022, through searches on the main scientific platforms, using the descriptors “vaping”, “adverse effects” and “e-cigarrette vapor”, chosen according to with DeCS (Descriptors in Health Sciences) and combining them with the Boolean operator “AND”. Results and discussion: through the aforementioned descriptors, 309 articles were found, of which 18 were selected for the integrative review and constitution of the final sample. In view of this, with the analysis of the aforementioned studies, it became evident that electronic cigarettes are related to the emergence of EVALI (E-cigarette or Vaping Product Use-Associated Lung Injury), with increased susceptibility to infections, cardiovascular diseases, cytotoxic and inflammatory effects, in addition to cerebrovascular impairment. Conclusion: given the above, it was concluded that the consumption of electronic cigarettes has systemic repercussions, at the pulmonary and extrapulmonary levels. With this, the study highlighted the implications of electronic cigarettes on the cardiovascular, respiratory, neural, genetic and immune systems, which affect the health and quality of life of the individual in a generalized way.